PUBLIC SECTOR REFORM IN HIGHER EDUCATION: THE APPLICATION OF NEW PUBLIC SERVICE PRINCIPLES IN ACADEMIC ADMINISTRATION - Kartinia Sari; Ina Iriyana; Farah Alifa; Sinta Cempaka (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study aims to assess the quality of academic services at the Faculty of Teacher Training and Education, University of Lampung, using the New Public Service (NPS) framework as a conceptual basis for public sector reform. Given the increasing demands for accountability, transparency, and responsiveness in higher education, the delivery of academic services requires a reconfiguration to reflect citizen-oriented values better better. Through a qualitative case study design, the study integrates data from interviews, observations, and document analysis to evaluate performance based on ten NPS-based indicators such as responsiveness, communication, accessibility, and sensitivity to user needs. The findings reveal several ongoing challenges, particularly related to staff communication gaps, limited accessibility, and lack of student engagement in the service evaluation process. Although human resources and infrastructure support serve as supporting elements, the lack of effective policy dissemination and the lack of user feedback mechanisms remain significant obstacles. The study emphasizes the need for a more collaborative, ethical, and participatory academic service model in higher education institutions. This research contributes both conceptually and practically to the public service reform discourse by illustrating the relevance of NPS principles in educational contexts, especially in developing countries where institutional adaptability and citizen participation are constantly evolving.